The Influence of The School Principal's Servant Leadership Style on Teacher Performance at State Vocational High School in Katingan Regency, Central Kalimantan Province - Hardian, Dafyar Eliadi; Sulistyaningrum, Wiwiek; Ni’mah, Istiqomah; Wuryani, Etti Dwi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the influence of the school principal's servant leadership style on teacher performance at SMK Negeri in Katingan Regency, Central Kalimantan Province. The background of this research is based on initial observations that revealed a discrepancy between the teachers’ favorable Performance Appraisal (SKP) scores and their actual daily performance, which still showed issues such as tardiness and low responsibility. This research employed a quantitative approach using a survey technique involving all teachers at SMA Negeri 3 Palangka Raya, totaling 73 individuals (total sampling). The research instrument was a closed-ended questionnaire using a Likert scale, measuring the dimensions of servant leadership (Dennis & Bocarnea) and teacher performance indicators (Ministry of Education, Culture, Research, and Technology). The results of the simple linear regression analysis indicate that the school principal’s servant leadership style has a positive and significant effect on teacher performance, with a coefficient of determination (R²) of 0.49. This means that 49% of the variation in teacher performance can be explained by the servant leadership style of the principal. These findings highlight the importance of service-oriented leadership in improving teacher performance.